Hubungan Hasil Belajar dan Self-Efficacy Dengan Literasi Lingkungan dalam Pembelajaran Biologi di SMA - Moza Hanu Sabila; Rohani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the relationship between learning outcomes and self-efficacy, both separately and jointly, with the environmental literacy of tenth-grade students in environmental conservation learning at SMA Negeri 1 Torgamba. This study used a quantitative correlational design with a sample of 71 students selected through cluster random sampling. The data were analyzed using Pearson Product Moment correlation and multiple correlation tests. The results showed a moderate relationship between learning outcomes and environmental literacy (r = 0.486; p = 0.000), a weak but significant relationship between self-efficacy and environmental literacy (r = 0.376; p = 0.001), and a simultaneous contribution of both variables of 23.7% to the variation in environmental literacy (R = 0.486; R² = 0.237; p = 0.000). Based on these results, it can be concluded that learning outcomes are a more dominant predictor than self-efficacy in shaping students’ environmental literacy. Keywords: Biology Learning, Environmental Literacy, Learning Outcomes, Self-Efficacy